Calidad y germinación de semillas de quinua Chenopodium quinoa willd. almacenadas artesanalmente por productores (2017)
This case study evaluated the conditions effect and traditional storage time of the quinoa producers of the Boyacá and Cundinamarca zone on the physical quality (color, shape, diameter, moisture content, imbibition) and physiological quality (viability, percentage And germination rate) of the seed. In addition, the effect of the substrate on the germinative power was determined for this species. The study was developed in the facilities of the Universidad de Ciencias Aplicadas y Ambientales U.D.C.A and in a local farm at “Buenos Aires” (municipality of Tibasosa, Boyacá, Colombia). The data analysis was carried out under a completely randomized design (DCA) with factorial arrangement 2x11 (Substrates x Samples); Meaning the combination of ecotypes by time and storage conditions. The study determined significant differences in the physical parameters of the seed of form, color and size, condition given to the seed mixture with which the crops normally develop in the zone. The physiological quality variables were affected by the storage conditions, because these sites can intervene in the acceleration of the metabolic processes of the seed causing the deterioration of the same. The substrate that provided the best conditions for the percentage and speed of germination of quinoa was the peat substrate, allowing a better use of the water and a greater aeration during the germination process. In this substrate the sample with the best performance corresponded to PCU12 with germination values greater than 80% in a period of 6 days and 7.36 seeds germinated per day, while in soil substrate this same sample did not reach 50% of germination during the 12 days and this same had a value of 3.37 for the germination rate variable.